2020
DOI: 10.3390/ijerph17041216
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mortality and Temperature in Two Northern Swedish Rural Parishes, 1860–1899—The Significance of Ethnicity and Gender

Abstract: The aim of this study was to analyze the association between season of birth and daily temperature for neonatal mortality in two Swedish rural parishes between 1860 and 1899. Further, we aimed to study whether the association varied according to ethnicity (indigenous Sami reindeer herders and non-Sami settlers) and gender. The source material for this study comprised digitized parish records from the Demographic Data Base, Umeå University, combined with local weather data provided by the Swedish Meteorological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…According to previous findings regarding the effect of temperature on neonatal health in sub-Arctic areas (Karlsson et al, 2020;Schumann et al, 2019), we expected a strong impact of low temperatures, especially among more resource-poor groups (farmers and workers) that would diminish over time. A declining effect was not clearly discernible in any social group due to the low vulnerability observed in the first decades of the twentieth century.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…According to previous findings regarding the effect of temperature on neonatal health in sub-Arctic areas (Karlsson et al, 2020;Schumann et al, 2019), we expected a strong impact of low temperatures, especially among more resource-poor groups (farmers and workers) that would diminish over time. A declining effect was not clearly discernible in any social group due to the low vulnerability observed in the first decades of the twentieth century.…”
Section: Discussionmentioning
confidence: 81%
“…From previous research regarding infant and neonatal mortality in historical populations, we know that season of birth affects the risk of mortality (Breschi & Livi-Bacci, 1997;Hare et al, 1981;Karlsson et al, 2019b;McEniry, 2011). In general, winter-born infants have higher neonatal mortality risk compared to summer-born infants (Dalla-Zuanna & Rosina, 2011;Healy, 2003;Karlsson et al, 2020), but an opposite pattern has also been found (Breschi & Livi-Bacci, 1997). For example, in Poland and Russia during the nineteenth century, the highest neonatal mortality was seen among summer-born infants, a pattern that might be associated with a higher workload among mothers during harvest seasons (Breschi & Livi-Bacci, 1997).…”
Section: Seasonality Temperature and Neonatal Mortalitymentioning
confidence: 95%
See 1 more Smart Citation
“…The studies cover a limited range of geographical locations and climate zones, with most studies from North America and Asia; only five studies were from low- and middle-income countries (LMICs) [ 19 , 28 , 29 , 30 , 31 ]. Most studies are conducted in urban populations, with five from rural areas, one of which was a combined urban-rural study [ 28 , 31 , 32 , 33 , 34 ]. Nine studies assessed the impact of temperature on all-cause infant mortality and five further studies assessed sudden infant death syndrome (SIDS) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies of health and mortality among the Sámi relate to a topic that is becoming increasingly important: that of climate and health. Barbara Schumann and others have studied the role of climatic factors for morbidity and mortality in Sweden since the 18th century, using DDB data, looking for factors modifying the impact of climate on health (Karlsson, Häggström Lundevaller, & Schumann, 2020;Oudin Åström, Edvinsson, Hondula, Rocklöv, & Schumann, 2016;Oudin Åström, Forsberg, Edvinsson, & Rocklöv, 2013;Rocklöv, Edvinsson, Arnqvist, Sjöstedt de Luna, & Schumann, 2014;.…”
Section: Disease and Health Risksmentioning
confidence: 99%